Problems in the regulation of a wrestler's body weight and the transition into a higher weight class - Shevtsov, A.; Galstyan, A.; Apoiko, R. (International Journal of Wrestling Science, 2013)
This is a case study of experimental weight gain by a 22 y old wrestler. In the experiment we assessed the level of physical properties (strength of different muscle groups), anaerobic and aerobic performance. The main objective was to gain quality muscle mass and strength, while preserving as much as possible of the other important physical properties of a wrestler: speed, agility, flexibility and endurance.